Persepsi Mahasiswa terhadap Pemanfaatan Media Pembelajaran Berbasis Teknologi Audio Video Visual dalam Perkuliahan Mata kuliah Pendidikan agama Islam - Lilik Nur Kholidah (Departement of Mathematics Education, 2023)
The use of learning media is an important aspect in the Islamic Education learning system. This attempt is a response to problems in delivering Islamic Education lecture materials which still use limited, conventional and unattractive learning media by some Islamic Education lecturers. By using a survey approach, this research collects information from respondents who are studying subjects in learning Islamic Education courses at Universitas Negeri Malang. The findings of this research show that students have a positive perception of the use of learning media based on audio video visual technology which is in connection with the learning objectives of Islamic Education courses, in connection with the characteristics of Islamic Education lectures, and makes it easier to understand Islamic Education lecture materials. This perception description is also a response to the condition of some students who do not understand the importance of using various learning media to gain learning experiences about Islamic values. The description of the perception of the use of learning media based on audio video visual technology in Islamic Education lectures is also a form of actualization of the implementation of the function of Islamic Education as a vehicle for instilling Islamic values that are relevant to technological developments so that learning can be personalized according to the needs and preferences of students.